2010
DOI: 10.1111/j.1600-0633.2009.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of juvenile Atlantic salmon (Salmo salar) body composition along sedimentary links*

Abstract: Johnston P, Bergeron NE. Variation of juvenile Atlantic salmon (Salmo salar) body composition along sedimentary links. 
Ecology of Freshwater Fish 2010: 19: 187–196. © 2010 John Wiley & Sons A/S Abstract –  The objective of this study was to determine the proximate body composition of juvenile Atlantic salmon along the sequence of aquatic habitat types created by longitudinal changes in the riverbed substrate of two rivers (i.e., sedimentary links units). Interesting trends in the body composition were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Finstad et al (2004) found that juvenile salmon with low energy content were less likely to survive winter, and these fish were also likely to have exhausted their TAG reserves. Habitat-specific differences in TAG accumulation in juvenile Atlantic salmon along a longitudinal gradient in a French river were reported by Descroix et al (2009), but no pattern was found in 2 Canadian rivers by Johnston and Bergeron (2010).…”
Section: Introductionmentioning
confidence: 82%
“…Finstad et al (2004) found that juvenile salmon with low energy content were less likely to survive winter, and these fish were also likely to have exhausted their TAG reserves. Habitat-specific differences in TAG accumulation in juvenile Atlantic salmon along a longitudinal gradient in a French river were reported by Descroix et al (2009), but no pattern was found in 2 Canadian rivers by Johnston and Bergeron (2010).…”
Section: Introductionmentioning
confidence: 82%